FUTURE TEACHER'S ABILITY TO CHOOSE A PEDAGOGICAL STRATEGY OF ACTIVITY IN AN INCLUSIVE EDUCATIONAL SPACE: SOME ASPECTS OF THE PROBLEM (Physical Culture and Sport: Scientific Perspective, 2025)
The article highlights the results of a scientific discussion on the problem of forming the ability of a future teacher to choose a pedagogical strategy of activity in the conditions of an inclusive educational space. The relevance of the specified problem in the context of modern educational transformations and the implementation of inclusive education is substantiated. Scientific approaches to defining the concepts of "inclusive education", "pedagogical strategy", "professional readiness of a future teacher" are analyzed. Based on the study of the best practices of leading universities and self-reflection of one's own practice, the main pedagogical strategies used in an inclusive educational environment are outlined, and the leading factors that influence the ability of a future teacher to make their conscious choice are specified. A generalization is made regarding the need for targeted formation of the specified ability in the process of professional training of future teachers. The purpose of the study is to theoretically substantiate the relevance of forming the ability, in particular, of a future physical education teacher to choose and implement a pedagogical strategy of activity in an inclusive educational space.Systemic, competency-based, personally oriented and inclusive scientific approaches constitute the methodological basis for understanding the segment of the research problem; these methodological guidelines directed efforts to comprehensively consider the professional activity of a physical education teacher in the conditions of the diversity of students' educational needs. The deepening of problematic issues regarding the ability to choose and implement a model of a pedagogical strategy of a physical education teacher in an inclusive environment was directed and comprehensively using the methods of questionnaires and pedagogical observation and analysis of the results of students' educational activities and their self-assessment of professional readiness. The implemented pedagogical tools contributed to the specification of the state of the ability of future physical education teachers to choose and implement a pedagogical strategy in the conditions of inclusive education. For example, the results of the ascertaining stage showed the predominance of medium and low levels of formation of the specified ability, which confirmed the need for targeted pedagogical influence on the outlined personal and professional quality of future physical education teachers. This prompted the scientific substantiation of the set of the most tangible influences of pedagogical conditions on the development of the ability to choose and implement a pedagogical strategy of activity in an inclusive educational space. Such conditions include: integration of the content of inclusive and adaptive physical culture into the content of relevant academic disciplines; use of situational modeling of physical culture lessons taking into account the nosological educational needs of students; involvement of students in reflective analysis of pedagogical situations during the implementation of educational and production practice. It is proved that the selected pedagogical strategy of teacher skill activity should be considered as a flexible system that integrates educational, health and socialization goals. It is based on the principles of adaptability and differentiation, naturally transforming the physical education of students from "normative" to "child-centered", confirming the important role of integrating inclusive issues into all components of the educational program for the preparation of education seekers, as well as the use of mostly interactive health-saving technologies that allow modeling real pedagogical situations, strengthening the ability of seekers to choose and implement a pedagogical strategy.
Keywords: pedagogical strategy; future physical education teacher; readiness; children with special educational needs; preparedness; preparation of a seeker in a higher education institution